Unraveling Nitrogen, Sulfur, and Carbon Metabolic Pathways and Microbial Community Transcriptional Responses to Substrate Deprivation and Toxicity Stresses in a Bioreactor Mimicking Anoxic Brackish Coastal Sediment Conditions - Dalcin Martins, Paula; Echeveste Medrano, Maider J.; Arshad, Arslan; Kurth, Julia M.; Ouboter, Heleen T.; Op den Camp, Huub J. M.; Jetten, Mike S. M.; Welte, Cornelia U. (Frontiers in Microbiology, 2022)
Microbial communities are key drivers of carbon, sulfur and nitrogen cycling in coastal ecosystems, where they are subjected to dynamic shifts in substrate availability and exposure to toxic compounds. However, how these shifts affect microbial interactions and function is poorly understood. Unraveling such microbial community responses is key to understand their environmental distribution and resilience under current and future disturbances. Here, we used metagenomics and metatranscriptomics to investigate microbial community structure and transcriptional responses to prolonged ammonium deprivation and sulfide and nitric oxide toxicity stresses in a controlled bioreactor system mimicking coastal sediment conditions. Candidatus Nitrobium versatile, identified in this study as a sulfide-oxidizing denitrifier, became a rare community member upon ammonium removal. The ANaerobic MEthanotroph (ANME) Ca. Methanoperedens nitroreducens showed remarkable resilience to both experimental conditions, dominating transcriptional activity of dissimilatory nitrate reduction to ammonium (DNRA). During the ammonium removal experiment, increased DNRA was unable to sustain anaerobic ammonium oxidation (anammox) activity. After ammonium was reintroduced, a novel anaerobic bacterial methanotroph species that we have named Ca. Methylomirabilis tolerans outcompeted Ca. Methylomirabilis lanthanidiphila while the anammox Ca. Kuenenia stuttgartiensis outcompeted Ca. Scalindua rubra. At the end of the sulfide and nitric oxide experiment, a gammaproteobacterium affiliated to the family Thiohalobacteraceae was enriched and dominated transcriptional activity of sulfide:quinone oxidoreductases. Our results indicate that some community members could be more resilient to stresses than others in coastal ecosystems, leading to dynamic microbial community shifts and novel functional states. Anaerobic methane and sulfide oxidation could be ecosystem functions preserved across the investigated disturbances, while differing nitrogen cycling pathways might be favored in response to stresses. These insights will help to understand and predict coastal ecosystem responses to future disturbances.